2016
DOI: 10.1542/peds.2016-1527
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Treatment in Children Transported to Tertiary Care: Recommendation Adherence and Outcomes

Abstract: Adherence to evidence-based recommended acute seizure treatment during initial care of pediatric patients using medical air transportation was poor. Intubation was more common when patients did not receive recommended acute seizure care. Educational efforts with a sustained quality focus should be directed to increase adherence to appropriate pediatric seizure treatment of children in community emergency departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…35 When benzodiazepines were administered, 22% (32 of 146) to 90% (159 of 176) of patients received suboptimal weight-based dosing. 22,25,26,28 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…35 When benzodiazepines were administered, 22% (32 of 146) to 90% (159 of 176) of patients received suboptimal weight-based dosing. 22,25,26,28 …”
Section: Resultsmentioning
confidence: 99%
“…24 Another study demonstrated a relative risk of intubation of 2.3 (95% CI, 1.4–3.9; p = 0.002) for pediatric patients treated with >2 benzodiazepine doses. 28 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations